Prevalence of nocturia and fecal and urinary incontinence and the association to childhood obesity: a study of 6803 Danish school children. Issue 3 (May 2019) - Warner, T.C.; Baandrup, U.; Jacobsen, R.; Bøggild, H.; Aunsholt Østergaard, P.S.; Hagstrøm, S.
Summary: Introduction: Fecal and urinary incontinence are common disorders in children. Obesity and its associated comorbidities have become increasingly common, and a relation between obesity, nocturia, incontinence, and nocturnal enuresis has been suggested. Objective: This large scale population study aims to determine the prevalence of fecal incontinence (FI), daytime urinary incontinence (DUI), nocturnal enuresis (NE), and nocturia in children at school entry and in adolescence and to clarify whether obesity is associated to any of the aforementioned symptoms. Study design: First-grade children and their parents and adolescents in the seventh to ninth grades were interviewed in relation to school nurse visits. The interview included questions on whether incontinence or nocturia were experienced at least once per month. The participants' age was recorded, and weight and height were measured. Body mass index (BMI) was calculated and age standardized by the use of BMI-standard deviation score (SDS), with reference to World Health Organization normative BMI data. Obesity was defined as BMI-SDS >2. Associations between obesity and incontinence and nocturia were quantified by odds ratio (OR). Results: Completed interview questionnaires and measurements were obtained from 4002 children (95.1%) in the child population and 2801 adolescents (84.4%) in the adolescent population. The mean age of children was 6.45 ± 0.39 years, and 4.4% were obese. Overall 11.2% reported FI, 21.8% DUI, 16.8% NE, and 31.4% experienced nocturia. Obesity was associated with FI in first-grade boys (OR 1.86 compared with normal weight). Mean age of adolescents was 13.9 ± 0.85 years, and 7.6% of adolescent boys and 5.5% of the girls were obese. Fecal incontinence was reported by 2.1% of the adolescents, 4.5% had DUI, 1.0% stated to have NE, and 32.3% reported nocturia. Obesity was significantly associated with nocturia in adolescents (OR 1.74–2.01). Discussion: The prevalence of nocturia seems constant throughout childhood and adolescent life; this has not previously been documented. Incontinence is very common at school entry, with DUI reported more frequently than enuresis by both children and adolescents. Obesity is associated with nocturia in adolescents and FI in first-grade boys, but no significant association between obesity and NE or DUI is found. Strength of this study is the very high participation rates, but the study does not reveal information on previous treatment, subtype, or severity of symptoms. Conclusions: Incontinence is very common in children. One-third of both children and adolescents experience nocturia. Obesity is associated with FI in first-grade boys and nocturia in adolescents.